An investigation of a jet-pump thermal (ice) storage system powered by low-grade heat - Worall, Mark (2001)
This thesis investigates a novel combination of a jet-pump refrigeration cycle and a thermal (ice) storage (TIS) system that could substantially reduce the electrical energy requirements attributable to comfort cooling.Two methods of TIS were identified; spray ice TIS would use evaporative freezing to store ice on a vertical surface,and encapsulated ice TIS would freeze a bed of encapsulated elements by sublimation freezing.Thestudy also investigates jet-pump refrigeration at partload and a convergent-divergent design manufactured from a thermoset plastic to make recommendations for performance enhancement for a system that has a low COP. An experimental rig was built to investigate the novel concepts in the laboratory.